Trigonometriyalıq teńlemeler dúziwde qatnasatuǵın ańlatpalar hám olardı túrlendiriw usılları - Izetaeva, G; Djanxodjaev, N; Erejepova, V; Kewnimjaeva, F (SCIENCE and SOCIETY, 2022)
This article discusses, more widely studied expressions involved in the construction of trigonometric equations, and methods for their interpretation.
Keywords: trigonometry; trigonometric equations; trigonometric functions; formulas for adding the product of trigonometric functions; irrational; radian